UPAYA PENINGKATAN INTERAKSI DAN AKTIVITAS BELAJAR DALAM PEMBELAJARAN KOSAKATA DENGAN STRATEGI ANALISIS FITUR SEMANTIK - Ari Kusmiatun (LITERA, 2005)
This study is aimed at improving the process of learning Indonesian, especiallythe vocabulary, by means of the feature analysis strategy as an appropriate strategy tomake students active and interactive in the learning process so that their vocabularymastery and, in turn, their communicative competence can improve.The subjects of the study were the second year students of Marketing StudyProgram, Vocational High School Abdi Negara Muntilan, Magelang. The steps in thestudy included problem identification, research design making, action, observation,and reflection. All were carried out in three cycles, each of which consisted of threeactions. The research data were both quantitative and qualitative. All participantswere involved in the data analysis to meet the criteria of data suitability comprisingthe democratic, process, and dialogic validity.The research findings show that the feature analysis strategy in the vocabularylearning can improve (1) students’ activity, 2) their interaction, and 3) their vocabularymastery. The various activities and the optimum interaction among students provethat their communicative competence is better.Key words: feature analysis strategy, vocabulary, activities, interaction